PENINGKATAN ASPEK PENGETAHUAN DAN PERILAKU ANAK SEKOLAH DASAR/MADRASAH IBTIDAIYAH MELALUI KOMIK BUSKI PADA TIGA DESA ENDEMIS FASCIOLOPSIS BUSKI DI KABUPATEN HULU SUNGAI UTARA, TAHUN 2003 - Anorital, Anorital; Kasnodihardjo, Kasnodihardjo; Dewi, Rita M.; Ompusunggu, Sahat (Media Penelitian dan Pengembangan Kesehatan, 2008)
Fasciolopsiosis is worm disease which is caused Fasciolopsis buski. The disease is an endemic at some villages in Hulu Sungai Utara Regency with prevalence 1.2-7.8%.The patients are children with age around 1-15 years old. In the year 2002-2003 have been carried out a research "Model of Control Fasciolopsis buski at South Kalimantan with Socio-Cultural Approach". In the first year (2002) of research, the data base of epidemiological and socio-cultural aspect, with cross sectional research design, have been collected. And in the second year (2003) has been done the intervention to the basic school students in three villages (Kalumpang Dalam, Putat Atas, and Talaga Mas), by doing a health campaign using comic books with Banjar language (local language). To find out the intervention has success, the researcher evaluated parasitological and socio cultural data collecting, especially knowledge, attitude and practice (KAP) aspect. Data collecting about KAP aspect was executed to the basic school students (grade 3-5). Total samples are 160 basic school students in those three villages. The result of parasitological data collecting in 3 villages after inten>ention is found a prevalence rate 5.2% positive fasciolopsiosis. There is decreased about 6.5% from 11.7% on the first year (2002) into 5.2% at second year (2003). The result of socio-cultural data collecting for KAP aspect as quantitative is found increase. There is knowledge increasing about the worm disease, where before intervention only 86.8% students who know the buski disease, and after intervention become 96.8%. While on practice aspect also increase, before intervention 73.1% basic school students use drugs worm (albendazol) and 84.3% after intervention, before intervention 48.7% students never eat raw water plants, after intervention become 19.9%, before intervention 57.5% students wash their hands with soap but after intervention raised up become 85.0% (p<0,05). The Conclusion is there is correlation between the intervention by doing health campaign using comic "buski" book (by local "Banjar" language) to basic school students and KAP aspect increasing. The suggestion of the research is there is a necessary needs to socialize aspects of good health living and "buski" disease (fasciolopsiosis) at basic school students through information which is appropriate with target and condition of the local area.